Synthesis and biological characterization of a promising F-18 PET tracer for vesicular acetylcholine transporter. Issue 15 (1st August 2015) - Tu, Zhude; Zhang, Xiang; Jin, Hongjun; Yue, Xuyi; Padakanti, Prashanth K.; Yu, Lihai; Liu, Hui; Flores, Hubert P.; Kaneshige, Kota; Parsons, Stanley M.; Perlmutter, Joel S.
Graphical abstract: Abstract: Nine fluorine-containing vesicular acetylcholine transporter (VAChT) inhibitors were synthesized and screened as potential PET tracers for imaging the VAChT. Compound 18a was one of the most promising carbonyl-containing benzovesamicol analogs; the minus enantiomer, (−)-18a displayed high potency (VAChT K i  = 0.59 ± 0.06 nM) and high selectivity for VAChT versus σ receptors (>10, 000-fold). The radiosynthesis of (−)-[ 18 F]18a was accomplished by a two-step procedure with 30–40% radiochemical yield. Preliminary biodistribution studies of (−)-[ 18 F]18a in adult male Sprague-Dawley rats at 5, 30, 60 and 120 min post-injection (p.i.) were promising. The total brain uptake of (−)-[ 18 F]18a was 0.684 %ID/g at 5 min p.i. and by 120 min p.i. slowly washed out to 0.409 %ID/g; evaluation of regional brain uptake showed stable levels of ∼0.800 %ID/g from 5 to 120 min p.i in the VAChT-enriched striatal tissue of rats, indicating the tracer had crossed the blood brain barrier and was retained in the striatum. Subsequent microPET brain imaging studies of (−)-[ 18 F]18a in nonhuman primates (NHPs) showed high striatal accumulation in the NHP brain; the standardized uptake value (SUV) for striatum reached a maximum value of 5.1 at 15 min p.i. The time–activity curve for the target striatal region displayed a slow and gradual decreasing trend 15 min after injection, while clearance of the radioactivity from the cerebellar reference region was much more rapid. Pretreatment of NHPs with 0.25 mg/kg of the VAChT inhibitor (−)-vesamicol resulted in a ∼90% decrease of striatal uptake compared to baseline studies. HPLC metabolite analysis of NHP plasma revealed that (−)-[ 18 F]18a had a good in vivo stability. Together, these preliminary results suggest (−)-[ 18 F]18a is a promising PET tracer candidate for imaging VAChT in the brain of living subjects.